Ai-Powered E-Commerce: Elevating E-Service Quality Through Utilitarian And Hedonic With E-Satisfaction As The Bridge To E-Loyalty - Yusrin, Nur Amalyna (Jurnal Multidisiplin Sahombu, 2025)
The advent of artificial intelligence (AI) has ushered in a new era in e-commerce, fundamentally transforming business operations and customer interactions. This study investigates the impact of AI on e-service quality, focusing on both utilitarian and hedonic dimensions, and examines the mediating role of e-satisfaction in fostering e-loyalty within the Indonesian e-commerce context. The primary research question addresses how AI-enhanced e-service quality influences e-satisfaction and, subsequently, e-loyalty. Despite the growing importance of AI in e-commerce, there has been limited research on its dual role in enhancing both functional and emotional aspects of e-service quality. This study employs a quantitative approach, utilizing Structural Equation Modeling (SEM) to analyze data collected through purposive sampling from consumers of major Indonesian e-commerce platforms. The findings reveal that AI significantly improves e-service quality by enhancing efficiency, reliability, and personalization, which in turn boosts customer satisfaction. Both utilitarian and hedonic improvements facilitated by AI contribute to higher levels of e-satisfaction, which strongly correlates with increased e-loyalty. Conclusively, this research highlights the pivotal role of AI in elevating e-commerce service quality, demonstrating that AI-driven enhancements in both functional and experiential aspects lead to greater customer satisfaction and loyalty. The implications for e-commerce businesses include the strategic use of AI to optimize customer experiences through personalized and efficient service delivery. As AI technologies continue to evolve, their potential to further enhance e-service quality and foster sustained customer loyalty presents significant opportunities for the future of e-commerce. This study provides valuable insights into the integration of AI in e-commerce, offering a roadmap for leveraging AI to achieve competitive advantage and customer retention.